2017
DOI: 10.1177/1010428317695526
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted - miR-423-5p knockdown enhances the sensitivity of glioma stem cells to apigenin through the mitochondrial pathway

Abstract: -423-5p knockdown enhances the sensitivity of glioma stem cells to apigenin through the mitochondrial pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Furthermore, in pancreatic cancer, miR-423-5p was either downregulated or upregulated with a significant inter-individual variation ( 28 ). However, miR-423-5p was demonstrated to be overexpressed in glioma tissues and corresponding glioma stem cells ( 29 ). In the present study, the ovarian tissue and plasma miRNA-423-5p levels in ovarian cancer patients were detected by RT-qPCR, and patients with ovarian endometriosis served as control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in pancreatic cancer, miR-423-5p was either downregulated or upregulated with a significant inter-individual variation ( 28 ). However, miR-423-5p was demonstrated to be overexpressed in glioma tissues and corresponding glioma stem cells ( 29 ). In the present study, the ovarian tissue and plasma miRNA-423-5p levels in ovarian cancer patients were detected by RT-qPCR, and patients with ovarian endometriosis served as control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-423-5p expression enhanced glioma cell proliferation, angiogenesis and invasion via targeting inhibitor of growth family member 4 and activating important signaling molecules, including AKT and extracellular signal-regulated kinase 1/2 ( 31 ). In another study, miR-423-5p knockdown notably enhanced the inhibitory effect of apigenin on the proliferation of glioma stem cells and the promotion of their apoptosis through the mitochondrial pathway ( 29 ). However, hepatocellular cancer cells transfected with miR-423-5p exhibited an increase in the S-phase population of the cell cycle, paralleled by a similar-size increase in autophagic cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our report is the first to identify the downregulation of miR-423-5p in the testis in response to scrotal hyperthermia. Previously, Wan et al reported that miR-423-5p knockdown correlated with reduced proliferation and increased mitochondria-dependent apoptosis among glioma stem cells [ 28 ]. Other studies found that miR-423-5p regulates gastric cancer cell proliferation and invasion [ 29 ] and promotes hepatocarcinoma cell autophagy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-423-5p is overexpressed in glioblastomas and contributes to glioma stem cells. The downregulation of miR-423-5p enhances apigenin-induced cell apoptosis in glioma stem cells with a shift in the Bax/Bcl-2 ratio, an increased cytochrome c level, Apaf-1 induction and caspase-3 activation [ 126 ]. In contrast, in malignant neuroblastoma SK-N-DZ and SK-N-BE2 cells, miR-138 overexpression significantly enhanced apigenin-induced cell apoptosis and decreased cell viability and colony formation capability in vitro and effectively suppressed tumor growth in vivo [ 127 ].…”
Section: Combination Therapy For Apigeninmentioning
confidence: 99%